PEMBERDAYAAN MASYARAKAT PESISIR MELALUI PRODUKSI STIK IKAN BARAKUDA SEBAGAI OLEH-OLEH KHAS PASAR SORKAM - Rumondang, Anne; Eddiwan, Eddiwan; Huda. J, Mhd Aidil; Batubara, Helfina Syam; Nisari, Tika (Universitas Mataram, 2025)
The abundance of barracuda fish catches that has not been optimally utilized, along with the low added value gained by the community, is a major issue faced by the people of Pasar Sorkam. Most of the fish are sold fresh without any processing, resulting in low selling prices and minimal impact on the fishermen’s economic improvement. Therefore, strategic efforts are needed to shift the community’s mindset towards creatively and sustainably managing marine resources. This activity aims to improve community skills in processing marine products, create economically valuable products, expand home-based businesses, and introduce Sorkam’s local culinary identity through the production of fish sticks. The implementation methods include socialization, training, production assistance, as well as creative and innovative product packaging and marketing. A participatory approach was used to involve the community actively in each stage, supported by local partners acting as key facilitators. The results show increased knowledge and skills among the community in processing barracuda into attractive and high-value products. The community also began to understand the importance of packaging and marketing strategies to attract both local and tourist consumers. The barracuda fish sticks are now being marketed locally and have received positive consumer responses. Furthermore, this initiative has fostered an entrepreneurial spirit, especially among coastal women who were previously not involved in productive and independent economic activities based on local resource potential. This activity successfully enhanced the skills and economic independence of the Sorkam community through the development of barracuda fish sticks as a distinctive regional souvenir.